Visualizing Research Trends in Positive Youth Development through Sport: a VOSviewer Bibliometric Analysis - Hidayat; Amung Ma'mun; Mustika Fitri; Agus Mahendra (Universitas Negeri Semarang, 2024)
Research and publications on positive youth development through sport instruction have been widely conducted in various countries. However, this trend does not always reflect the existing conditions. In fact, positive youth development through sport has a significant positive impact on the younger generation. This study aims to analyze the visualization metrics of publications on positive youth development through sport over the past ten years (2013-2023) using the literature review method. Examination using Scopus through the Publish or Perish (PoP) application found only twelve articles (out of a total of 74 articles) that met the VOSviewer visualization analysis criteria. The results of the study showed that the highest publications occurred in 2021 with 56 citations, and in 2018 with 55 citations from two articles each year. VOSviewer visualization confirms that positive youth development through sport instruction has great potential to be further developed with other terms, so that it can more effectively meet the needs of the younger generation. This study presents the results of computational bibliometric mapping of data published in research articles. Future research could consider broader aspects of PYD teaching and link it to other terms to enhance the various aspects that support positive adolescent development.